Smart ZnO decorated optimized engineering materials for water purification under natural sunlight. (10th October 2020) - Le Pivert, Marie; Zerelli, Brahim; Martin, Nathan; Capochichi-Gnambodoe, Martine; Leprince-Wang, Yamin
Graphical abstract: Highlights: Zinc oxide nanostructures grew onto engineering materials by hydrothermal synthesis. Depending on substrate, different mechanisms and optimal growth times were observed. Obtention of total degradation of organic dye in water by UV-light photocatalysis. Optimized samples demonstrated an excellent photocatalytic activity under sunlight. Abstract: Developing and designing smart civil engineering materials for environmental depollution in our daily life is a major issue. ZnO nanostructures implemented onto civil engineering material surfaces by low cost hydrothermal growth could be one of the most promising solutions, and already showed a good water purification efficiency by photocatalysis under UV light. Nevertheless, there are two main factors to work out in order to simplify and intensify the photocatalyst production on engineering materials. The first one is the reduction of the growth time. The second one is the use of sunlight, which is the most abundant, clean, and renewable light source available. However, reducing the growth time might have an impact on the photocatalytic efficiency due to the surface/volume ratio modification. In this work, a short and efficient hydrothermal synthesis (2 h or 1 h 30 min vs 4 h) was used to grow ZnO nanostructures directly on non-conventional substrates such as tiling and concrete, demonstrating an excellent photocatalytic activity for organic pollutant degradation in water under natural sunlight, even during cloudy days. Decreasing the growth time showed no significant influence on tiling samples and even increased their photocatalytic efficiency until the optimal value obtained with a growth time of 2 h. A strong impact of the shorter growth time was observed on concrete samples, as reducing the growth time leads to complex ZnO nanosheet structures with a lower gap value (3.11 eV for 1 h 30 min against 3.17 eV for 4 h) due to a possible influence of the surface pH value and the complex chemical composition of concrete.